1997
DOI: 10.1055/s-2007-973708
|View full text |Cite
|
Sign up to set email alerts
|

Tuberous Sclerosis Complex: The Role of Neuroradiology

Abstract: Tuberous Sclerosis Complex is the second commonest phakomatosis affecting between 1 in 70,00-10,000 live births. It is a multisystem disorder but neurological disturbances are often the presenting feature and cause major morbidity/mortality. In this paper the neuroradiological and clinical features are reviewed, focusing on a rational approach to imaging children with tuberous Sclerosis Complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…While it has been shown that MRI fails to detect SENs in up to a third of those individuals who show SENs on CT (a more sensitive modality for detecting calcified SENs), this increased sensitivity is of no known prognostic value. 22 MRI remains the test of choice for screening in patients with TSC.…”
Section: Discussion How Does a Sgct Differ From A Sen?mentioning
confidence: 99%
“…While it has been shown that MRI fails to detect SENs in up to a third of those individuals who show SENs on CT (a more sensitive modality for detecting calcified SENs), this increased sensitivity is of no known prognostic value. 22 MRI remains the test of choice for screening in patients with TSC.…”
Section: Discussion How Does a Sgct Differ From A Sen?mentioning
confidence: 99%
“…Why some of the lesions enlarge is not well understood. Contrast-enhanced MR imaging is more sensitive than CT for tumor identification [1, 2]. A new focal neurological deficit, increased intracranial pressure, changes in motion or uncontrolled seizures may be signs of a growing tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are variable pathological findings in multiple systems, the main cause of morbidity and mortality and the most prominent feature of this disease are neurological disturbances. In the cerebral parenchyma, subependymal hamartomas and cortical tubers occur by the overgrowth of astrocytes [1]. …”
Section: Introductionmentioning
confidence: 99%
“…Up to now, no valid explanation has been proposed, while 88% to 95% of patients with TSC present SENs, [9,45] and about one child with TSC out of ten will develop SGCT(s). Exceptionally, SGCTs have been described in other ventricular compartments than the foramen of Monro, such as the lateral ventricle wall [2] or the temporal horn. [49] Elsewhere, extremely rare cases of neonatal SGCTs have contributed to our incomprehension of tumorigenesis and call in question again the supposed fi liation SEN-SGCT.…”
Section: Filiations Sen-sgctmentioning
confidence: 99%
“…TSC, also known historically as Bourneville's disease (1880), has been initially described by von Recklinghausen in 1862, while Vogt (1908) reported the typical and characteristic clinical triad of the disease associating facial angiofi bromatosis, epilepsy and mental retardation. [1,2] TSC is one of the more common single gene disorders, with an incidence of one in 5800 to 6000 live births, a prevalence of one in 30 000 and a frequency of one per 150 000 live births. [3,4] There is neither ethnic linking nor differences according to gender.…”
Section: Introductionmentioning
confidence: 99%